Memorial formativo: as vivências profissionais e acadêmicas dentro e fora da faculdade - LOPES, Tiago Tavares (2024)
The aim of this memorial is to highlight the experiences cultivated throughout the Information Systems course, providing a brief account of the reasons that led me to choose the program, my initial impressions, and the challenges faced in the early stages. The focus is on the professional and academic experiences gained in two significant stages: participation as a scholarship holder at Infocentro-UFPA and working as technical support at ENZO Automatizando. I present both positive and negative memories that have contributed to my academic and professional development over these years. The methodology applied in this work involves the retrieval of memories and experiences lived from the choice of the course to the two jobs that were of utmost importance for the formation of the professional I am today. This retrieval will be done through narratives and photographs of my own authorship, aiming to further emphasize the events.